SEGMENTASI PELANGGAN BERDASARKAN PRODUK MENGGUNAKAN METODE K- MEDOIDS - Putri Eka Prakasawati; Yulison H Chrisnanto; Asep Id Hadiana (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Market segmentation is a division of consumer groups that have different needs, characteristics and behaviors (heterogeneous) in a particular market so that it becomes a homogeneous market unit, in this case it is very helpful in a more targeted marketing process so that company resources can be used effectively and efficient for example makes it easy to distinguish markets and recognize competitors with the same segment. CV. Lampegan Jaya is a company engaged in the distribution of food and beverage products including Meses Tulip Chocolate, Vita Zone, Bintang Sobo Tea, Preso Tea, Okky Jelly Drink, Fruit Tea, Bima Energy Nails, Coptic Cappuccino, Mizon and My Tea. These products are distributed to outlets spread across Bandung, Cianjur, Cileunyi, Cimahi, Soreang and Sumedang. Distribution of products is carried out based on the demand for outlets for the product. In this study a system of classifying customer segmentation based on products. This system can classify customers based on the number of purchases and area. The process of this customer grouping system uses a K-Medoid clustring algorithm to classify customers based on segmentation on the product purchase amount and area. With test data of 6 regions, 600 customer data and 28 products. Keywords: Market Segmentation, k-Medoids, , Food Products